Strategy for Implementing the New Bandung Integrated Manpower Management Application (New Bimma) in Increasing Employment Opportunities in the City of Bandung - Suci Azizah Febriyani; Utang Suwaryo; Dede Sri Kartini (Journal of Law, Politic and Humanities, 2025)
Quality public services are related to continuous innovation. For public sector organizations, innovation is a demand amidst changes in people's lives. In fact, local governments need to innovate to improve the quality of their public services. In Indonesia, the city of Bandung has one of the innovations in overcoming the number of unemployed in the form of the New Bandung Integrated Manpower Management Application or New Bimma. This study aims to examine and analyze the strategies carried out by the Bandung City Manpower Office in implementing New Bimma in increasing employment opportunities. This study applies a descriptive qualitative approach with data collected through observation, interviews, and document studies. The analysis focuses on Mulgan's (2009) strategy theory which contains the stages of purpose, environment, direction, action, and learning. The results of the study show that in general the existing stages show an increase or development even though there are some shortcomings and obstacles.